(untitled) (Central Asian Journal of Medical Sciences, 2021)
Objective: To describe the demographics, nature of the injury and visual outcomes of pediatric patients presenting with traumatic cataract requiring surgery at the National Center for Maternal and Child Health in Mongolia and to compare the relevant literature on traumatic pediatric cataracts in other countries. Methods: The charts of individuals aged ≤ 18 years who underwent surgery for traumatic cataract over a two-year period at a pediatric hospital were reviewed. The data collected included: demographic information, mode and time of injury, intraocular lens type, surgeries pre- and post-operative best-corrected visual acuity, and surgical complications. Results: Over the 2-year study period, 27 children underwent cataract surgery for traumatic cataract. The mean age was 8.52 ± 4.7 years (range, 1-17 years). The type of primary insult was penetrating injury in over 80% of patients. The mean interval between injury and cataract surgery was 7 ± 6.5months. Pre-cataract surgery no patient had vision better than 20/40; after cataract surgery 36% had 20/50. Conclusion: A better understanding of the causes of eye injuries and the environments in which they occur can provide informed educated strategies for parents, caregivers, and teachers and can possibly reduce time to treatment.